Efektivitas Bekam Basah Untuk Penurunan Nyeri Sendi di Desa Temboro Kabupaten Magetan - Anggraini, Devita Anugrah; Kartika; Alkasanah, Adhin (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Joint pain is a sign that is often complained about by people with gout, joint pain occurs due to the deposition of uric acid crystals in the joints caused by high uric acid in the blood exceeding normal limits so that the blood in the body settles into urate crystals which cause swelling, redness, and pain. The purpose of this study was to determine the effectiveness of wet cupping to reduce joint pain in Temboro Village, Magetan Regency. The research design used Pre experiment with one group pretest posttest design. The sampling technique used in this study was purposive sampling with a sample size of 18 respondents. The tools used in data collection are observation sheets, NRS (Numeric Rating Scale) pain scale measuring instruments. The results of the study with the Wilcoxon Signed Rank Test of joint pain before and after being given wet cupping obtained a p-value of 0.000 (α = 0.05), this shows a significance value of <0.05 which means that there is an effectiveness of wet cupping to reduce joint pain. Wet cupping for 2 times within 2 weeks can reduce joint pain. Therefore, cupping can be used as an alternative nonpharmacological treatment for joint pain. Where wet cupping plays a role in reducing the intensity of pain felt by stimulating nerve fibers through pressure, touch, or vibration.